Isoflavones and anti-inflammatory constituents from the fruits of Psoralea corylifolia. (November 2017) - Chen, Chiang-Hsiang; Hwang, Tsong-Long; Chen, Li-Chai; Chang, Tsung-Hsien; Wei, Chun-Sheng; Chen, Jih-Jung
Abstract: The fruits of Psoralea corylifolia, known as Psoraleae Fructus ( Buguzhi in Chinese), are traditionally used for the treatment of spermatorrhea, nephritis, asthma, pollakiuria, and various inflammatory diseases. Three previously undescribed isoflavone derivatives, 7- O -methylcorylifol A, 7- O -isoprenylcorylifol A, and 7- O -isoprenylneobavaisoflavone, have been isolated from the fruits of P. corylifolia, together with 9 known compounds. The structures of these compounds were determined through spectroscopic and MS analyses. Among the isolated compounds, 7- O -methylcorylifol A and psoralen exhibited potent inhibition (IC50 values ≤ 10.89 μM) of superoxide anion generation by human neutrophils in response to N -formyl-L-methionyl-L-leucyl-L-phenylalanine/cytochalasin B (fMLP/CB). 7- O -Isoprenylcorylifol A, 7- O -isoprenylneobavaisoflavone, and 12, 13-dihydro-12, 13-epoxybakuchiol inhibited fMLP/CB-induced elastase release with IC50 values ≤ 14.30 μM. In addition, 7- O -isoprenylcorylifol A, bakuchiol, 12, 13-dihydro-12, 13-epoxybakuchiol, and psoralidin showed potent inhibition with IC50 values ≤ 36.65 μM, against lipopolysaccharide (LPS)-induced nitric oxide (NO) generation. Graphical abstract: Image 1 Highlights: Three previously undescribed isoflavones were isolated from the fruits of Psoralea corylifolia. Their chemical structures were determined on the basis of extensive spectroscopic analysis. The isolated compounds were evaluated for anti-inflammatory activity.